Measurements of the Upsilon(1S), Upsilon(2S), and Upsilon(3S) differential cross sections in pp collisions at root s=7 TeV - (:unkn) unknown (ELSEVIER, 2015)
Differential cross sections as a function of transverse momentum p(T) are presented for the production of Upsilon(nS) (n = 1, 2, 3) states decaying into a pair of muons. Data corresponding to an integrated luminosity of 4.9 fb(-1) in pp collisions at root s = 7 TeV were collected with the CMS detector at the LHC. The analysis selects events with dimuon rapidity vertical bar y vertical bar < 1.2 and dimuon transverse momentum in the range 10 < p(T) < 100 GeV. The measurements show a transition from an exponential to a power-law behavior at p(T) approximate to 20 GeV for the three Upsilon states. Above that transition, the Upsilon(3S) spectrum is significantly harder than that of the Upsilon(1S). The ratios of the Upsilon(3S) and Upsilon(2S) differential cross sections to the Upsilon(1S) cross section show a rise as p(T)-increases at low p(T), then become flatter at higher p(T). (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: CMS; Upsilon; B-Physics; Cross section; QED RADIATIVE-CORRECTIONS; UNIVERSAL MONTE-CARLO; PHOTOS; DECAY